The Efficacy, Safety and Tolerability of Canakinumab in the Treatment of Familial Mediterranean Fever: A Systematic Review of the Literature - Kacar M (Dove Medical Press, 2020)
Mark Kacar,1 Sinisa Savic,1 Jeroen CH van der Hilst2,3 1Department of Clinical Immunology and Allergy, St James´s University Hospital, Leeds, UK; 2Department of Infectious Diseases and Immunity, Jessa Hospital, Hasselt, Belgium; 3BIOMED Research Institute, University of Hasselt, Hasselt, BelgiumCorrespondence: Jeroen CH van der HilstDepartment of Infectious Diseases and Immunity, Jessa Hospital, Stadsomvaart 11, Hasselt 3500, BelgiumTel +32 11309485Email jeroen.vanderhilst@jessazh.beAbstract: Familial Mediterranean Fever (FMF) is the most prevalent genetic autoinflammatory disorder. In most patients, treatment with colchicine can prevent attacks of fever and inflammation. However, 5%– 10% of patients are resistant to colchicine treatment, while a similar percentage cannot tolerate colchicine in doses needed to prevent attacks. For these patients, Canakinumab, a full human antibody against IL-1β, has been approved recently by the FDA and EMA. In this article, we present a systematic review of the long-term efficacy, safety, and tolerability of Canakinumab in FMF patients who cannot tolerate colchicine or who are resistant to colchicine treatment.Keywords: familial mediterranean fever, Canakinumab, anti-IL1 therapy